UMA CONTRIBUIÇÃO PARA AVALIAÇÃO DA QUALIDADE DE SERVIÇO DE ATENDIMENTO AO CONSUMIDOR (SAC): ESTUDO DE CASO EM UMA EMPRESA DE TELEATENDIMENTO. - Maciel Júnior, Licínio dos Santos (2007)
This work makes an analysis the Inmetro´s methodology used for the evaluation of the Services of Attendance to the Consumer telephony´s call center in the Program of Evaluation of Products. The work intends to answer the problem: The Inmetro´s methodology used in the Program of Evaluation of Products can develop the Quality Management of the telephony´s call center? The hypotheses are tested: The Inmetro´s methodology is arguable since it does not present significant differences of the attendance´s monitor used for the searched company; As much the Inmetro´s methodology how much the attendance´s monitor used for the searched company is arguable in the scope of the Quality Management, therefore does not contemplate, in its design philosophy TQM. One concluded that the used methodology for the Inmetro and the attendance monitor does not contemplate philosophy TQM for not consulting the expectations and necessities of real consumers. However the used the Inmetro´s methodology for the develops the quality management in the measure where the call center the specific subjects can use it to evaluate the knowledge of the operation in relation, identifying chances for future training, thus contributing for the continuous improvement of the attendance.